Responses of vegetation green-up date to temperature variation in alpine grassland on the Tibetan Plateau. (September 2019) - Li, Xiaoting; Guo, Wei; Chen, Ji; Ni, Xiangnan; Wei, Xiaoyi
Highlights: Minimum temperature played a dominant role in controlling the green-up date of alpine grassland on the Tibetan Plateau. Minimum temperature in spring had greater impact on the GUD than that in winter. Difference in minimum temperature between winter and spring may be a novel indicator for spring onset in alpine grassland. Abstract: Temperature increases in spring can advance vegetation green-up date (GUD) due to the increased heat accumulations. However, temperature increases in winter will delay the GUD due to the postponed fulfilment of chilling requirements. Such contrasting impacts of temperature changes in spring and winter on the GUD have been documented from many ecosystems in the Northern Hemisphere. However, the combined effects of temperature variations in winter and spring on the GUD remained unclear, especially in the cold Tibetan Plateau. To advance our understanding of how alpine grassland GUD responds to climate warming, this study evaluated 14 years of field GUD observations of sedge species Kobresia humilis on the Tibetan Plateau. The results showed that January and March-April were two critical periods in determining the long-term GUD variations. The minimum temperatures (Tmin ) during these two critical periods played the dominant roles in controlling the GUD. Increases in the Tmin significantly shifting the GUD by −3.9 days °C −1 and 1.7 days °C −1 in the spring and winter, respectively. Moreover, Tmin in March-April played a more important role in determining the GUD than did Tmin in January. In addition, the difference in minimum temperature (ΔTmin ) between these two critical periods of January and March-April might be a novel indicator for vegetation GUD. This study provides novel insights into the differential impacts of minimum temperatures in winter and spring on the GUD and how they should be explicitly considered to better understand the effects of climate change on vegetation phenology.